Calcium supplementation in CVVH using regional citrate anticoagulation. Issue 1 (4th February 2019) - Zheng, Yin; Xu, Zhongye; Fan, Qichen; Zhu, Qiuyu; Ma, Shuai; Lu, Jianxin; Zhuang, Feng; Hao, Guihua; Lu, Wei; Ding, Feng
Abstract: Introduction : Calcium supplementation is one of the most important factors in maintaining the safety and efficacy of regional citrate anticoagulation (RCA) during continuous renal replacement therapy (CRRT). The aims of this study were to assess the determinants of calcium requirements in RCA‐CVVH and to simplify the calcium supplementation approach. Methods : Our study consisted of two parts. The first part was a discovery phase to determine the key factors of calcium supplementation. Twenty critically ill patients who required RCA‐CVVH were enrolled in this part. Systemic citrate, total calcium, protein‐bound calcium, and ionized calcium concentrations were serially measured using the traditional RCA protocol. A two‐phase calcium supplementation protocol was then proposed, and algorithms were developed for calcium supplementation. The second part of the study was the validation phase. Another 97 critically ill patients were enrolled and were treated with RCA‐CVVH using the new version of the calcium supplementation protocol. Findings :The loss of calcium flux in the extracorporeal circuit and the increase in citrate‐calcium complexes in vivo were the main determinants of the required calcium supplementation. In the CVVH mode, the rate of calcium infusion had to be reduced after systemic citrate level reached a steady state. With the aid of mathematical models, systemic calcium levels could be stably maintained in the normal range, and the frequencies of calcium monitoring were reduced. Discussion :Calcium supplementation during RCA‐CVVH undergoes two phases. We propose mathematical models to quantify the need for calcium supplementation, which enable individualization of the RCA prescription and simplify the management of RCA in the CVVH mode.